Meaning of storytelling in volunteers' experiences at Pabukon Ngadongeng Community Reading Park - Anwar, Rully Khairul; Rukmana, Evi Nursanti; Saepudin, Encang; Khadijah, Ute Lies Siti; Vanamamalai, Ratnamala (Universitas Padjadjaran, 2023)
The Pabukon Ngadongeng Community Reading Park is a library that has storytelling services to enhance children's literacy and cultural knowledge. Volunteers assisted the Community Reading Park to develop children's creativity and imagination with stories. This research aimed to determine the meaning of storytelling among volunteers at the Pabukon Ngadongeng Community Reading Park by analyzing the experience and meaning of storytelling. The research method used qualitative with a phenomenology approach. The study result showed that the experience of storytelling for volunteers consisted of expanding children's story reading, interaction with readers, language development, cultivating imagination, creativity, entertainment, and sharing knowledge. The meaning of storytelling in the volunteers consisted of volunteers' motivation, the impact of storytelling on volunteers, the impact of storytelling on the relationship with readers, contributions of storytelling to volunteers' personal development, and the involvement of volunteers in the development of the Community Reading Park. It also included challenges and obstacles faced by volunteers in storytelling, volunteers' perception of the impact of storytelling on children's education and literacy, meaningful storytelling, teaching without preaching and preserving cultural stories. In conclusion, volunteers have assisted Pabukon Ngadongeng Community Reading Park with storytelling services for children. Children have imagination and creativity, and their language development improves. Volunteers provide fun learning experiences for children through storytelling, including practicing reading and writing literacy programs for children.